Prevalence and factors associated with the use of potentially inappropriate medications for elderly patients with acute heart failure (Revista Contexto & Saúde, 2023)
Acute heart failure (AHF) is a complex clinical syndrome, the therapeutic management of which requires the use of polypharmacy, which can increase the risk of using potentially inappropriate medications (PIM) for the elderly. We sought to evaluate the prevalence and factors associated with the use of PIM by hospitalized elderly with a diagnosis of AHF. AHF, admitted to a public hospital, in the years 2019 and 2020, with at least 48 hours of hospitalization. Clinical, sociodemographic and pharmacotherapeutic data were collected. MPIs were classified according to the Beers Criteria, 2019 update. The association between dependent and independent variables was performed through crude and adjusted analysis, using the binary logistic regression model. A total of 135 patients were included, with a predominance of males (53.6%), mean age 74.74±9.66, arterial hypertension (90.9%) and excessive polypharmacy (50.4%). The prevalence of PIM was 98.5%, mean 3.83±1.64. The main therapeutic classes of PIM were those intended for the cardiovascular system (45.18%) and the alimentary tract and metabolism (30.20%). There was a significant association between the number of PIM and excessive polypharmacy (PR=11.748; CI=3.691-37.391). There is a need for interventions and safe practices for the use of medicines in the elderly, insertion of the clinical pharmacist with the multidisciplinary team, aiming to minimize the use of PIM in the elderly and the associated risks, given the high prevalence of the use of these drugs, associated excessive polypharmacy in this population.